Discharge FGF23 levels predicts one year outcome in patients admitted with acute heart failure. (14th October 2021) - Aimo, A; Vergaro, G; Taurino, E; Del Franco, A; Fabiani, I; Prontera, C; Masotti, S; Musetti, V; Emdin, M; Passino, C
Abstract: Background: Patients with acute heart failure (AHF) show high levels of fibroblast growth factor-23 (FGF23) on admission. We examined if plasma FGF23 changes during an episode of AHF, and if FGF23 holds prognostic significance in this setting. Methods: Consecutive AHF patients were enrolled. Blood samples were collected on admission and at discharge. Patients were then followed for all-cause death or HF hospitalization. Results: Patients (n=125; median age 76 years [interquartile interval 71–83], 63% men, left ventricular ejection fraction 35% [25–56%]) had median admission FGF23 70 ng/L (47–100), N-terminal pro-B-type natriuretic peptide (NT-proBNP) 5, 844 ng/L (2, 503–10, 468), high-sensitivity troponin T (hs-TnT) 40 ng/L (25–72), and soluble suppression of tumorigenesis-2 (sST2) 26 ng/mL (17–37). While other biomarkers decreased, FGF23 increased by 15% from admission to discharge (p=0.033), with a significant correlation with percent changes in estimated glomerular filtration rate (rho=0.306, p=0.001). Over a 12-month follow-up, 64 patients (51%) experienced the endpoint. They were more often men, older, with higher systolic pulmonary artery pressure (sPAP), higher NT-proBNP, hs-TnT and discharge FGF23. The best FGF23 cut-off at discharge from receiver operating characteristics analysis was 78 ng/L. Both discharge FGF23 and the 78 ng/L cut-off independently predicted outcome in models including gender, sPAP, age, and 1) admission NT-proBNP, 2) discharge NT-proBNP, 3) admission NT-proBNP and hs-TnT, 4) discharge NT-proBNP and hs-TnT. The 78 ng/L cut-off also refined risk reclassification. Conclusions: During an AHF episode, FGF23 increases from admission to discharge, and patients with higher discharge FGF23 have a higher risk of worse outcome. Funding Acknowledgement: Type of funding sources: None.